Configuration of integration features of genetic determinism systems of erythrocyte antigens in patients with oral lichen planus - Reshetnyk, Людмила Леонідівна; Shumynska, Тетяна Анатоліївна (Actual Dentistry, 2024)
Relevance. Over the past few years, the number of patients with oral lichen planus (OLP) has almost doubled due to the increase in aggressive forms of OLP with a possible risk of malignancy. Only a few isolated studies indicate a genetic determinism for OLP, but more often these data were obtained based on insufficiently adequate and modern research methods, which complicate the correct interpretation of the obtained results. Purpose: to study the presence of genetic determinism of erythrocyte blood antigens to oral lichen planus. Materials and methods. The patients were divided into 2 groups—the main group—278 patients at OLP (aged 26–65 years) and the control group—298 people (blood donors), where dental diseases, as well as diseases of internal organs and systems were excluded. The groups were homogeneous in terms of age and gender. Clinical-radiological, immunogenetic and statistical methods were applied. Research results. The erosive form of OLP was associated with group 0(I) in 54.2±0.4% of cases, and the hyperkeratotic form was combined with group 0(I) only in 28.7±1.8% of cases. B (ІІІ) and AB (IV) groups were less often associated with the erosive form of OLP and were observed in 17.3±0.1 and 2.0±0.1% of cases, respectively. The integration of the A(II) group with the erosive form of OLP was significantly lower than with 0(I) carriers and amounted to 30.5 0.1%, but the indicator was higher than in individuals with B (III) and AB (IV) groups The hyperkeratotic form of OLP was more often observed in A(II) carrier than in 0(I) and was 44.1±0.1% versus 28.7 1.8%, respectively. With blood group B(ІІІ), the relationship with OLP is not traced. Conclusion. A correlative relationship was established with erythrocyte blood antigens of the ABO system in patients with OLP. Detailed risk groups for the development of erosive and hyperkeratotic forms of ChPL in patients with pathology of the gastrointestinal tract O(I)> A(II)> (III)—with erosive form and A(II)> O(I)> B(III) )—with hyperkeratosis. Keywords: oral mucosa, oral lichen planus, erythrocyte blood systems, genetic determinism.